Pengaruh Deferred Tax Assets, Financial Distress, Dan Kualitas Audit Terhadap Tax Avoidance - Agnes Adelia Leonardus; Kathryn Sugara (MDP Student Conference, 2026)
This study aims to analyze the influence of deferred tax assets, financial distress, and audit quality on tax avoidance in financial sector companies listed on the Indonesia Stock Exchange for the 2021–2024 period. A quantitative approach was used with secondary data obtained from the companies' annual reports. The analytical method used was multiple linear regression after testing the classical assumptions. The results showed that financial distress had a negative effect on tax avoidance. Deferred tax assets and audit quality had no effect on tax avoidance. Simultaneous testing showed that all three independent variables jointly influenced tax avoidance. This finding implies that a company's financial condition is the primary factor in determining tax avoidance policies, while accounting and audit oversight factors have not yet become the main determinants.